(untitled) (REMUNOM, 2024)
Criminal expertise is the forensic police area responsible for investigating a crime. It is present from the scene of death to the appropriate analysis procedures to conclude the case. The biomedical criminal expert works in the following areas: toxicology, ballistics, documentoscopy, papiloscopy, and forensic genetics. This professional can work within hematology with biological traces and a very specific crystallographic technique, the Teichmann method, which differentiates human blood from other substances.This text reports the role of the biomedical expert in the identification and analysis of human blood collected at the crime scene, justifying its importance in resolving criminal cases and identifying those involved in the criminal action, including victims and suspects. A bibliographical review research based on the important role of biomedics in criminal expertise, forensic hematology, and confirmatory tests was conducted, utilizing virtual platforms: APCF, CRBM, CFBM, Google Scholar, RBC, and JUS Brasil. The review included national and international published articles from 2019 to 2023.Biomedicine focused on the forensic area is a multidisciplinary science efficiently applied by biomedical professionals in forensic hematology. It deals with the characteristics of the traces most often found at a crime scene that, after being detected, must be confirmed regarding the presence or absence of human hemoglobin. This process is carried out using a highly specific and sensitive method, the Teichmann technique, which forms crystals through the heating effect and chemical reaction of the material.It is ratified as a protagonist in the role of the biomedical professional at the crime scene, particularly in the identification of human blood, due to their laboratory knowledge and training.